2015
DOI: 10.1371/journal.pone.0132322
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Neural Processing of Risky Decisions: Effects of Sex and Behavioral Disinhibition

Abstract: BackgroundAccidental injury and homicide, relatively common among adolescents, often follow risky behaviors; those are done more by boys and by adolescents with greater behavioral disinhibition (BD).HypothesisNeural processing during adolescents' risky decision-making will differ in youths with greater BD severity, and in males vs. females, both before cautious behaviors and before risky behaviors.Methodology/Principal Findings81 adolescents (Patients with substance and conduct problems, and comparison youths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…The authors found that the OFC in females was more dynamically engaged than males during task performance (Lee et al 2009): while there were no correlations between neural activity and behavior in males, there was a negative correlation between neural activity in the OFC and choice of the uncertain reward when preceded by a punished outcome (i.e., no reward delivery) and a positive correlation between OFC neural signal and choice of the uncertain outcome when preceded by a uncertain, but unpunished, outcome. Interestingly, in a recent study (Crowley et al 2015), males had greater OFC activation than females prior to making safe choices in another risk-based decision-making task. These last two studies suggest that the OFC in females may be more selectively tuned to process punishment and uncertainty whereas the OFC in males may be more selectively recruited to process information regarding safe reinforcement.…”
Section: Potential Explanations For Sex Differences In Decision-makingmentioning
confidence: 90%
“…The authors found that the OFC in females was more dynamically engaged than males during task performance (Lee et al 2009): while there were no correlations between neural activity and behavior in males, there was a negative correlation between neural activity in the OFC and choice of the uncertain reward when preceded by a punished outcome (i.e., no reward delivery) and a positive correlation between OFC neural signal and choice of the uncertain outcome when preceded by a uncertain, but unpunished, outcome. Interestingly, in a recent study (Crowley et al 2015), males had greater OFC activation than females prior to making safe choices in another risk-based decision-making task. These last two studies suggest that the OFC in females may be more selectively tuned to process punishment and uncertainty whereas the OFC in males may be more selectively recruited to process information regarding safe reinforcement.…”
Section: Potential Explanations For Sex Differences In Decision-makingmentioning
confidence: 90%
“…Ventral and paralimbic cortical regions implicated, i.e. OFC, insular and temporopolar cortices, are associated with affective processing and regulation, self-awareness, stimulus-reinforcement associations, behavioral control and risky decision making (Clark et al 2008; Craig 2002; Crowley et al 2015; Etkin et al 2011; Fellows 2007; Kringelbach and Rolls 2004; Manes et al 2002; Modinos et al 2009; Muhlert and Lawrence 2015; Rolls 2004; Van Leijenhorst et al 2010; Xue et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Such alternatives force risky-vs.-cautious decisions. Unfortunately, many decision-making brain structures are hypoactive as adolescents with substance and/or conduct problems process risky-vs.-cautious decisions (Crowley et al, 2015; Heitzeg et al, 2014; Jones et al, 2016; Shanmugan et al, 2016). Reported regions have included, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To assess that possibility we examined in elementary-school children the association between severity of externalizing behavior and regional intensity of neural activation during risky-vs.-cautious decision-making, using the same decision-making game that we had employed earlier in adolescents with severe substance and conduct problems (Crowley et al, 2015). Seeking children with minimal or no substance exposure, we recruited 9–11 year-olds, since many children who will develop substance problems are using regularly by age 13 (Young et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation